Concept and Self-Consciousness of the žemininkai Generation - Kvietkauskas, Mindaugas (Literatūra, 2022)
The article analyses the origins of the concept of the žemininkai generation (the so-called Earth generation of Lithuanian literary modernism), in order to assess the validity and suitability of this traditional concept for the research of Lithuanian literature and culture. The notion that the group that published the literary anthology Žemė (Earth, 1951) represents a much wider literary and cultural generation born in the 1920s has been established in Lithuanian literary studies since the 1950s, but it has not been sufficiently critically examined. From a socio-cultural point of view, the question arises as to whether this actually corresponds to an authentic collective phenomenon of generational consciousness of these authors. For this purpose, the development of the concept of the žemininkai generation in the post-war Lithuanian diaspora and post-soviet Lithuania is investigated, the concept of generation formulated in the cultural sociology works of Karl Mannheim and Norbert Elias is discussed, and cases of generational identification in the early texts of the žemininkai, written during the Second World War, and in their later ego-documentary texts are analysed. Aspects of critical period experience, generational solidarity, socio-cultural location, intergenerational relations, and literary impact are considered. It is concluded that the expression of a complex generational self-consciousness indeed appears in the texts of the žemininkai group.
Keywords: žemininkai generation; generational consciousness; Lithuanian literature; cultural sociology; modernism